Thrombolysis and clinical outcome in patients with stroke after implementation of the Tyrol Stroke Pathway: a retrospective observational study. Issue 1 (January 2015) - Willeit, Johann; Geley, Theresa; Schöch, Johannes; Rinner, Heinrich; Tür, Andreas; Kreuzer, Hans; Thiemann, Norbert; Knoflach, Michael; Toell, Thomas; Pechlaner, Raimund; Willeit, Karin; Klingler, Natalie; et al.
Summary Background Intravenous thrombolysis for ischaemic stroke remains underused worldwide. We aimed to assess whether our statewide comprehensive stroke management programme would improve thrombolysis use and clinical outcome in patients. Methods In 2008–09, we designed the Tyrol Stroke Pathway, which provided information campaigns for the public and standardised the entire treatment pathway from stroke onset to outpatient rehabilitation. It was commenced in Tyrol, Austria, as a long-term routine-care programme and aimed to include all patients with stroke in the survey area. We focused on thrombolysis use and outcome in the first full 4 years of implementation (2010–13). Findings We enrolled 4947 (99%) of 4992 patients with ischaemic stroke who were admitted to hospitals in Tyrol; 675 (14%) of the enrollees were treated with alteplase. Thrombolysis administration in Tyrol increased after programme implementation, from 160 of 1238 patients (12·9%, 95% CI 11·1–14·9) in 2010 to 213 of 1266 patients (16·8%, 14·8–19·0) in 2013 (ptrend 2010–13<0·0001). Differences in use of thrombolysis in the nine counties of Tyrol in 2010 (range, 2·2–22·6%) were reduced by 2013 (12·1–22·5%). Median statewide door-to-needle time decreased from 49 min (IQR 35–60) in 2010 to 44 min (29–60) in 2013; symptomatic post-thrombolysis intracerebral haemorrhages occurred in 28 of 675 patients (4·1%, 95% CI 2·8–5·9) during 2010–13. In four Austrian states without similar stroke programmes, thrombolysis administration remained stable or declined between 2010 and 2013 (mean reduction 14·4%, 95% CI 10·9–17·9). Although the 3-month mortality was not affected by our programme (137 [13%] of 1060 patients in 2010 vs 143 [13%] of 1069 patients in 2013), 3-month functional outcome significantly improved (modified Rankin Scale score 0–1 in 375 [40%] of 944 patients in 2010 vs 493 [53%] of 939 in 2013; score 0–2 in 531 [56%] patients in 2010 and 615 [65%] in 2013; ptrend 2010–13<0·0001). Interpretation During the period of implementation of our comprehensive stroke management programme, thrombolysis administration increased and clinical outcome significantly improved, although mortality did not change. We hope that these results will guide health authorities and stroke physicians elsewhere when implementing similar programmes for patients with stroke. Funding Reformpool of the Tyrolean Health Care Fund.